The Optimal Timing and Duration of Daily G‐CSF for the Primary Prevention of Febrile Neutropenia in Breast Cancer Patients Undergoing Adjuvant TAC Chemotherapy - Kim, Zisun; Hur, Sung Mo; Lee, Jong Eun; Han, Sun Wook; Jung, Hae Il; Kim, Sung Yong; Lee, Jihyoun; Lim, Cheol Wan (Asia-Pacific journal of clinical oncology, 2025)
ABSTRACT Aim TAC chemotherapy is a standard adjuvant treatment for early‐stage breast cancer, with G‐CSF recommended for preventing febrile neutropenia (FN). This study investigates the optimal initiation timing for daily filgrastim to prevent FN in patients undergoing TAC chemotherapy, a subject not fully explored in existing guidelines. Methods Sixty breast cancer patients receiving adjuvant TAC chemotherapy were randomly assigned to start daily filgrastim either on Day 2 (Day 2 group, n = 30) or Day 5 (Day 5 group, n = 30). The primary outcome was the incidence of FN. Secondary outcomes included the duration of neutropenia treatment and the neutropenia profile. Results Patients underwent 349 cycles of TAC chemotherapy (173 cycles in Day 2 group and 176 cycles in Day 5 group). The incidence of FN was significantly lower in the Day 2 group (6.4%, 11/173) compared to the Day 5 group (22.2%, 39/176, p < 0.0001). Additionally, the mean ± SD duration of filgrastim treatment was longer (8 ± 1 vs. 6 ± 1 days, p < 0.0001), and the duration of severe neutropenia was shorter (3 ± 1 vs. 4 ± 1 days, p = 0.001) in the Day 2 group. Conclusion Initiating filgrastim on Day 2 of TAC chemotherapy significantly enhances its effectiveness in preventing FN compared to starting on Day 5. These findings support early intervention and sustained treatment to optimize toxicity management in adjuvant TAC chemotherapy. The study aimed to determine the optimal timing and duration of filgrastim administration for the primary prevention of febrile neutropenia (FN) in breast cancer patients undergoing adjuvant TAC chemotherapy. Our findings suggest that initiating daily filgrastim from Day 2 and continuing for 7 days optimizes toxicity reduction. This information is valuable for clinicians and healthcare professionals involved in the treatment of breast cancer, enhancing the management of adjuvant TAC chemotherapy.